Tar conversion over olivine and sand in a fluidized bed reactor using toluene as model compound. (1st December 2017) - Morin, Mathieu; Nitsch, Xavier; Pécate, Sébastien; Hémati, Mehrdji
Highlights: Experimental study on toluene conversion at 850 °C in a fluidized bed reactor. Effect of solid medium (sand or olivine) and reactive atmosphere (H2 and H2 O). Toluene conversion is dependent on the PH2 /PH2O ratio in the reactor. Characterization of olivine particles by SEM-EDX and XRD analyses. The catalytic effect of olivine is related to the presence of Fe 0 on its surface. Abstract: The aim of this work is to study the tars conversion in conditions representative of biomass gasification in a fluidized bed reactor. Experiments are conducted at 850 °C and atmospheric pressure in a fluidized bed reactor with toluene as tar model. Influences of the nature of the media (sand and olivine) and of the reactive atmosphere (steam and hydrogen partial pressures) on toluene conversion are particularly studied. The steam and hydrogen partial pressures were varied in the range of 0.05 to 0.4 bars and 0 to 0.2 bars, respectively. Results showed a strong influence of these parameters on toluene conversion. Olivine was found to have a catalytic activity towards steam reforming reactions which depends on the ratio P H 2 / P H 2 O in the reactor. Both thermodynamic equilibrium and surface analyses (EDX and XRD) of olivine particles suggested that this ratio controls the oxidation/reduction of iron at the olivine surface. Besides, iron is more active towards tars removal when its oxidation state is low. At 850 °C and P H 2 / P H 2 O > 1.5, the iron is reduced to form native iron (Fe 0 ) on the olivine surface which favors the steam reforming of toluene.